Una nueva especie de Acanthoscurria (Araneae: Theraphosidae: Theraphosinae) sin órgano estridulador, del sur de Perú - Ferretti, Nelson (2016)
Acanthoscurria sacsayhuaman sp. nov. (Araneae: Theraphosidae) is described based on a male from Cusco, Peru. The new species is characterized by the absence of stridulatory bristles on retrolateral face of palpal trochanter. Moreover, it can be distinguished by morphology of the male palpal bulb and tibial apophysis of the first pair of legs. The genus is recorded for the first time for Peru.